(untitled) (Journal of Social Sciences Review, 2024)
The ongoing struggle is crucial to counteract the disintegration faced by many in contemporary society, as well as to eliminate discrimination, racial bias and social inequalities that perpetuate the injustices and inequities characterizing our world. We undertook this study to scrutinize the textbook Islmaiyat’s content, particularly the knowledge and values, for the eighth-grade, with the aim of fostering the moral development of students. Khyber Pakhtunkhwa’s Islamiyat textbooks served as the sole focus of the study. This qualitative study employed the interpretive paradigm and utilized content analysis to examine Islamiyat at the eighth-grade level. The researcher utilized Imam Ghazali’s Islamic philosophy and Kohlberg’s moral development theory as the theoretical foundation for this investigation. We gathered data from the Islamiyat textbook for grade VIII in the academic year 2022-23. The researchers manually analyzed the data using content analysis and coding methods. The research pinpointed the themes of moral development that emerged from the contents of textbook Islamiyat grade VIII which were;Quran and Hadiths. These themes encompassed fundamental beliefs, acts of worship, Uswa Hasanah, the importance of global values, Islamic history, and the inculcation of moral values in contemporary society. The study advised revising the textbook to correct certain technical errors and enhance its utility for students’ moral development.